International Legal Framework for the Regulation of Misleading Advertising of Dietary Supplements on Social Media : Consumer Protection and Prevention of Nutrition Misinformation - Bártová, Tereza; Čajka, Radek, 1983-; Semenenko, Vadim; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
The current situation on the social media and Instagram platform in particular concerning occasional unfair behaviour of producers and sellers of nutritional supplements can cause decrease in customers´ loyalty to the company or an individual standing behind the business, inefficient wasting of buyers´ money and, in some severe cases, even health damage. These situations are not only economically inefficient, unfair from the marketing and business point of view, unethical from the social perspective, but also on the border of illegality if the health of an individual is threatened. The main reason for this diploma thesis to be written is raising awareness about this issue that might be unintentionally overlooked by experts in many connected disciplines: law, marketing, nutrition, ethics, cyber security on social media and others. Its purpose is to find the reason why such cases of fraud have a chance to happen at all, define them and intent to find the appropriate solution to the problem that could be as relevant and real as possible, so that it could be implemented directly to any corresponding channel with predispositions to have a real impact on the matter.
Vedoucí práce: Radek Čajka
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses